Interactive Multimedia Innovation on Short Distance Running Materials in Junior High School - Setyawan, Herwindo; Sunardi, Sunardi; Ardianto, Deny Tri (Journal of Education Technology, 2022)
Innovation in the field of education must be in accordance with the developments and demands. The first step in improving the quality of education is through innovation in the learning process, by integrating the use of ICT-based learning media into the learning system. Therefore, this study aims to explore the need for the development of ICT-based learning media for short-distance running materials in junior high schools. This study applies a descriptive qualitative. The research sample consisted of 83 class VIII students and 2 subject teachers. Data collection techniques used field studies, interviews, and needs analysis questionnaires, while the instruments used observation sheets, questionnaire, and a list of questions. The research results will be analyzed interactively through data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that during the implementation of learning, teachers tend not to use learning media. Print modules still dominate their use in learning (43.4%). Innovations related to interactive multimedia appear when participants feel attracted to a learning media that is complex and flexible in its operation. The results of the questionnaire showed that 80.7% of students were interested in the presence of interactive multimedia in physical learning and sports, and of course this was the first step to implementing an innovative learning activity. So the results of this study indicate that an innovation is needed through the development of digital learning media, as a means to improve the quality of the process and learning outcomes.